Design of Experiment - Optimization of HPLC Analysis of Vitamin A and E in Margarine and Vegetable Oil - Garai, Lorinc (Journal of Food Technology Research, 2017)
Liquid chromatography is a useful method for selective analysis of vitamin A and E. The native components can be easily tested due to their UV-absorbance and beneficial separation characteristics. To test the food sample, vitamin A and E have to be separated from the fatty part of food. This step is performed by saponification, which is the critical step of procedure due to the heat and light sensitivity of both vitamins. The corresponding standards (MSZ-EN 12822-1, MSZ EN 12823-1) recommend a wide range of saponification temperature and time, giving an opportunity to optimize the recovery of the analyte. Experimental tests were performed from vegetable oil and margarine sample to find the temperature and time settings for the best recovery. Both factors were examined with centered two-level factorial design. Data analysis showed an increasing recovery of analytes towards the corner points of highest possible temperature and shortest possible saponification time. Finally, confirmatory tests were made.